2003
DOI: 10.1159/000074173
|View full text |Cite
|
Sign up to set email alerts
|

Gene arrangement at the Rhesus blood group locus of chimpanzees detected by fiber-FISH

Abstract: The Rhesus (Rh) blood group system in humans is encoded by two genes with high sequence homology. These two genes, namely, RHCE and RHD, have been implied to be duplicated during evolution. However, the genomic organization of Rh genes in chimpanzees and other nonhuman primates has not been precisely studied. We analyzed the arrangement of the Rh genes of chimpanzees (Pan troglodytes) by two-color fluorescence in situ hybridization on chromatin DNA fibers (fiber-FISH) using two genomic DNA probes that respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…This chimpanzee individual was used for the chimpanzee genome project. Other studies have investigated copy number variation at a limited number of individual loci among the genomes of several chimpanzees to gain insight into the dynamics of corresponding human CNVs (15,18). However, a genome-wide analysis of CNVs in a chimpanzee sample population is still lacking.…”
mentioning
confidence: 99%
“…This chimpanzee individual was used for the chimpanzee genome project. Other studies have investigated copy number variation at a limited number of individual loci among the genomes of several chimpanzees to gain insight into the dynamics of corresponding human CNVs (15,18). However, a genome-wide analysis of CNVs in a chimpanzee sample population is still lacking.…”
mentioning
confidence: 99%
“…As mentioned before, Suto et al (2003) reported the existence of two-Rh-gene and four-Rh-gene types in chimpanzees. It is likely that PTB-1 ( fig.…”
Section: Resultsmentioning
confidence: 61%
“…We sequenced the region surrounding exon 7 (∼860 bp) from 12 chimpanzees ( P. troglodytes verus ), 3 bonobos ( P. paniscus ), 3 gorillas ( Gorilla gorilla ), 1 orangutan ( Pongo pygmaeus ), and 2 siamangs ( Symphalangus syndactylus ). Five (“Akina,” “Aluku,” “Chiko,” “Kanao,” and “Mikota”) of the 12 chimpanzees were the same individuals used in the Suto et al (2003) fiber-FISH analysis. Two primers on intron 6 (forward: 5′-TTT GCA TAT GTG TCC ACA TCT G-3′) and on intron 7 (reverse: 5′-GCC AAC AAA TAT TCA CCG AAG C-3′) were used for each PCR experiment and sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RH gene homologues have been detected in all mammals studied [687] . Like most humans, chimpanzees and gorillas have at least two RH genes, although some chimpanzees have three or four genes; other primates, including orangutans and gibbons, old world and new world monkeys, and prosimians, have only one RH gene per haploid genome [689,690] . The cDNA sequences demonstrated a high degree of homology to the human sequence and predicted proteins of 417 amino acids.…”
Section: Rhd and Rhcementioning
confidence: 99%